Design, fabrication and testing of a portable gravity generator as a back-up power source. Issue 1 (March 2021) - Agustin, R.; Alonzo, C; Ami, K; Brual, J M; Viray, D N; Maglaya, A; Fernando, A
Abstract: In this study a prototype small scale gravity driven generator was designed, tested, and evaluated. The prototype was designed using readily available components. It uses a chain sprocket system and a 24V DC generator. This study might help the needs for a new sustainable energy source, a gravity driven device that harness energy from a falling mass might provide an alternative solution for an increasing energy demand and supply electricity to remote areas.